2018
DOI: 10.1038/s41598-018-28716-z
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for excessive osteoclast activation in SIRT6 null mice

Abstract: SIRT6 is a NAD-dependent histone 3 deacetylase. SIRT6 null mice have been reported suffering osteopenia. However, the role of SIRT6 in bone resorption is still not well understood. In this study, we focused on the role of SIRT6 in osteoclast. We performed histological analysis on the femur, spine, alveolar bone and even tail of mutant mice, and found the bone mass is sharply decreased while the osteoclast activity is significantly increased. These phenotypes were further demonstrated by the osteoclast differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 39 publications
(77 reference statements)
2
22
0
Order By: Relevance
“…The increased expression of this cell fusion molecule offers a possible explanation for the giant multinucleated osteoclast phenotype that was observed in TRAP-positive cells. Our result was in accordance with several previous studies that the change of osteoclast size and nuclei number sometimes is inconsistent with that of osteoclast number in the process of osteoclastogenesis [49][50][51][52]. The different expression pattern of the genes might suggest that diverse mechanisms are involved in the METTL3-mediated regulation of osteoclast differentiation.…”
Section: Discussionsupporting
confidence: 92%
“…The increased expression of this cell fusion molecule offers a possible explanation for the giant multinucleated osteoclast phenotype that was observed in TRAP-positive cells. Our result was in accordance with several previous studies that the change of osteoclast size and nuclei number sometimes is inconsistent with that of osteoclast number in the process of osteoclastogenesis [49][50][51][52]. The different expression pattern of the genes might suggest that diverse mechanisms are involved in the METTL3-mediated regulation of osteoclast differentiation.…”
Section: Discussionsupporting
confidence: 92%
“…SIRT6 encodes a member of the sirtuin family of NAD-dependent enzymes that are implicated in cellular stress resistance, genomic stability, aging, and energy homeostasis. A recent study demonstrated that the way SIRT6 regulated osteoclast was predominantly through osteoblast paracrine manner, rather than osteoclast-autonomous behavior, which provided a valuable insight into the pathogenesis of osteoporosis due to SIRT6 mutation (Zhang et al, 2018). Metabolite Acetyl-T2 toxin is the class of organic compounds known as trichothecenes.…”
Section: Discussionmentioning
confidence: 99%
“…Not surprisingly, bone mineral density and cancellous and cortical bone volume are much reduced in SIRT6−/− compared to control mice [27,28]. Histomorphometric analysis performed in 3-week-old mice revealed impaired bone formation, while effects on resorption remain controversial [27,29]. Ex-vivo osteoblast and osteoclast cell cultures from SIRT6−/− mice suggest that Sirt6 contributes to osteoblast and osteoclast formation.…”
Section: Sirt6mentioning
confidence: 97%